A contrastive study of three graphite anodes in the piperidinium based electrolytes for lithium ion batteries. (February 2016) - Jiang, Xiao-Tao; Wang, Chen-Yi; Gao, Kun; Niu, Li-Li; Li, Shu-Dan
Graphical abstract: The fitting results of R sei and R ct of three graphite/Li cells. Besides three graphite/Li cells show the similar R sei, the NG198/Li cell demonstrates a higher R ct value in all test temperatures. Especially, the R ct at 333 K is even up to 355.8 Ω cm 2 . Obviously, the narrow distribution of edge plane for NG198 caused this result, and then greatly restricts its cell capacity. By contrast, CMB with bigger specific surface area and more Li + insertion points shows lower resistance at room temperature, which should help to improve its capacity. Highlights: SEI film is closely related to graphite structures and formation temperature. The graphite with bigger surface area and more Li + insertion points behaves better. The graphite with narrow edge plane is uncompetitive for ionic liquid electrolyte. Abstract: The electrochemical behaviors of natural graphite (NG198), artificial graphite (AG360) and carbon microbeads (CMB) in an ionic liquid based electrolyte are investigated by cyclic voltammetry (CV). The surface and structure of three graphite materials are characterized by scanning electron microscope (SEM) and X-ray diffraction (XRD) before and after cycling. It is found that solid electrolyte interface (SEI) is closely related to graphite structure. Benefiting from larger specific surface area and more dispersed Li + insertion points, CMB shows a better Li + insertion/de-insertion behavior than NG198 and AG360. Furthermore, electrochemical impedance spectra (EIS) prove that the SEI of different graphite electrodes has different intrinsic resistance and Li + penetrability. By comparison, CMB behaves better cell performances than AG360, while the narrow edge plane makes NG198 uncompetitive as a potential anode for the ionic liquids (ILs)-type Li-ion battery.